PERAN UMKM (USAHA MIKRO KECIL MENENGAH) DALAM PEMBANGUNAN EKONOMI BANGSA - Alfarizi Ramadhan; Muhammad Arif Barus (CV. ADIBA AISHA AMIRA, 2023)
Micro, Small and Medium Enterprises (MSME) activities are one of the business sectors in the national economy that can grow and develop sustainably. Micro, small and medium enterprises are a good platform for job creation jointly planned by the government, the private sector and individual entrepreneurs. The role of society in national development, the main bodies of economic development are small, medium and micro businesses. The position of small, medium and micro businesses in the national economy plays an important strategic role. The aim of this research is to determine the role of MSMEs in economic development. The results of this research show that small, medium and micro businesses have made a major contribution to the development of the national economy. Even though there are still challenges in the implementation process, the government is working hard to provide several stimulus measures to overcome these problems. so that small, medium and micro businesses can continue to develop. Regarding the contribution and role of small, medium and micro businesses, the government must continue to strengthen support for small, medium and micro businesses so that their pillar role in national economic development can be utilized optimally